Replies Vestibular Stimulation Al irritative Heat In Normal Subjects 100 - Mendivil D., Juan A. (1967)
In order to obtain quantitative factors normal vestibular reactions in individuals in our midst , in part using the procedure described in vestibulograma (Tables Nos. 1, 2 ) used in the Department of Otolaryngology , Faculty of Medicine, San Fernando , this study was conducted. For the practical aspect of the art we selected thermal test with some peculiarities in his art, so that is comfortable in its execution and easy in its final interpretation. The objective of this task is proposed to determine vestibular responses to thermal stimuli in normal individuals , setting values ​​of response pattern. The present investigation was happy collaboration of enthusiastic disciples of Professor Dr. Reynaldo V. Salazar , as well as nurses and employees of the Hospital Materno Infantil San Bartolome , whose contribution thank very sincerely . We hope this small task prove useful both among specialists and general practitioners in one of the most extensive and interesting aspects of otology .